Analysing the transformation of higher education with ict. An exploratory study on teaching beliefs and teaching practices with ict in latin american universities - Brenda Barros; Margarita Chavarría; Joaquín Paredes (Revista Electrónica Interuniversitaria de Formación del Profesorado)
It highlights the need to promote a change in teaching at university, the characteristics of this change in teaching practices, more participatory and open, and the contribution of information and communications technology (ICT). It presents an exploratory qualitative study – based on two cases of university teaching practices in Latin America– of teacher beliefs and uses of ICT in their teaching. The results of analysis of the cases highlights the importance of teachers’ pedagogical beliefs in the uses of ICT. A model for analyzing these practices is proposed.